Light irradiation helps magnetotactic bacteria eliminate intracellular reactive oxygen species. (24th August 2017) - Li, Kefeng; Wang, Pingping; Chen, Chuanfang; Chen, Changyou; Li, Lulu; Song, Tao
Summary: Magnetotactic bacteria (MTB) demonstrate photoresponse. However, little is known about the biological significance of this behaviour. Magnetosomes exhibit peroxidase‐like activity and can scavenge reactive oxygen species (ROS). Magnetosomes extracted from the Magnetospirillum magneticum strain AMB‐1 show enhanced peroxidase‐like activity under illumination. The present study investigated the effects of light irradiation on nonmagnetic (without magnetosomes) and magnetic (with magnetosomes) AMB‐1 cells. Results showed that light irradiation did not affect the growth of nonmagnetic and magnetic cells but significantly increased magnetosome synthesis and reduced intracellular ROS level in magnetic cells. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) was performed to analyse the expression level of magnetosome formation‐associated genes ( mamA, mms6, mms13 and mmsF ) and stress‐related genes ( recA, oxyR, SOD, amb0664 and amb2684 ). Results showed that light irradiation upregulated the expression of mms6, mms13 and mmsF . Furthermore, light irradiation upregulated the expression of stress‐related genes in nonmagnetic cells but downregulated them in magnetic cells. Additionally, magnetic cells exhibited stronger phototactic behaviour than nonmagnetic ones. These results suggested that light irradiation could heighten the ability of MTB to eliminate intracellular ROS and help them adapt to lighted environments. This phenomenon may be related to the enhanced peroxidase‐like activity of magnetosomes under light irradiation.